Revisiting "Institutions": A Study of the Evolution of Institutional Analysis. Issue 2 (3rd April 2018) - Almeida, Felipe
Abstract: Since its founding in 1967, the Journal of Economic Issues (JEI) has been the main publication vehicle for original institutionalist studies. In 1987, twenty years after JEI's establishment, volumes 3 and 4 of the journal were dedicated to the reintroduction of key concepts and analytical frameworks of original institutionalism. In 1987, JEI's volume 3, Walter Neale's "Institutions" was published. It is a seminal study on the meaning and identification of institutions that introduced key issues from the original institutionalism analytical framework. As three decades have passed since the publication of Neale's article, there is significant motivation to analyze the evolution of the meaning and identification of institutions through original institutionalist studies. The main sources of information for this article are related works published in JEI in the last thirty years.